Peran Bahasa Arab dalam Memahami Ilmu Agama Islam: Analisis tentang Pentingnya Bahasa Arab dalam Menggali Ajaran Islam - Azmi, Dzaki; Nuraeni, Neni (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Arabic is the original language of the Qur'an, Hadith, and various other classical literature, which are the main sources of Islamic teachings. Arabic plays a very important role in understanding Islamic religious knowledge. This study also aims to explain the importance of mastering this language for all Muslims, especially in terms of education and the development of Islamic knowledge. This research was conducted through a qualitative descriptive analysis that included a review of various relevant scientific sources. The results show that mastering Arabic enables one to understand religious texts correctly, avoid misinterpretations, and gain a contextual understanding that is in accordance with the original intent of the author or narrator.